Small Intestinal Sarcoidosis Causing Intestinal Obstruction: A Rare Case Report from Vietnam - Vinh Phu, Pham; That Hung, Ton; Ba Lap, Duong; Phuc Minh, Nguyen; Vinh Hung, Tran (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2022)
Abstract: Sarcoidosis is a systemic disorder represented by the formation of non-caseating granulomas throughout the body. Extrapulmonary sarcoidosis is uncommon, around 10% of all cases. Most instances of GI sarcoidosis affect the stomach, while data revealing small bowels participate in only 0,03% of all sarcoidosis cases. Herein we are reporting a unique case of a 45-year-old Vietnamese female patient who underwent an emergency of acute small bowel obstruction due to isolated ileal sarcoidosis. This paper is one of the few reports on the topic. Keywords: sarcoidosis, non-seating granulomas, intestinal obstruction.